Estudo de caso do potencial de rejeito das Minas Três Riachos e Diniz - Soares, Jadson Batista (Universidade Federal Rural do Semi-Árido, 2017)
The creation of new tools since the prehistory period was essential for human survival. With this, it is necessary a search of natural resources with specific characteristics necessary for the creation of tools. However, demand needs to be handled cautiously, since our sources of resources are limited. Thus, it is necessary to have a previous study of the area, to identify the type of mineral that can be extracted from the site, aiming at sustainability. Evaluate that in the municipality of Jardim de Piranhas, located in the state of Rio Grande do Norte, located in the region of Seridó, which has a population of fourteen thousand seven hundred and thirty four inhabitants according to IBGE (2016) data, it has a territory rich in Mineral resource. The applied methodology consisted of a brief bibliographical study and an acquisition of data of the proximities of the municipality through field visits, sample collection and obtaining information through a miner (A) who had already worked in one of the analyzed areas, in addition, the mapping of the route was carried out to understand the location of each area studied. As a result, the proximity between the studied deposits, the presence of copper ore (Cu) and scheelite. In addition, a cost estimate was made taking into account only the gain obtained from the sale of the wastes.
Keywords: Potencial minério; Extração mineral; Jardim de Piranhas - RN; Scheelita; Mina Diniz; Potential ore; Mineral extraction; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA